276 CIRCULATING FORMS OF PLASMA TRANSTHYRETIN IN PATIENTS WITH WILD-TYPE TRANSTHYRETIN AMYLOIDOSIS AND EFFECTS OF TREATMENT WITH TAFAMIDIS. (15th December 2022) - Chiara, Sanguinetti; Minniti, Marianna; Panichella, Giorgia; Vergaro, Giuseppe; Aimo, Alberto; Castiglione, Vincenzo; Caponi, Laura; Paolicchi, Aldo; Emdin, Michele; Franzini, Maria
Abstract: Introduction: Transthyretin (TTR) is a homotetrameric 55-KDa plasma protein that transports thyroxin and retinol complexed to retinol-binding protein (RBP). TTR misfolding and aggregation can lead to the extracellular deposition of amyloid (ATTR) representing one of the most frequent forms of amyloidosis in elderly. Aim of this study is to develop a native electrophoretic method to characterize circulating TTR in plasma samples of ATTR patients before and during treatment with tafamidis, a TTR stabilizer. Methods: Plasma from ATTR patients (n=6), collected before (T0) and during tafamidis treatment, and plasma of healthy controls (n=6) were obtained from Fondazione Toscana G. Monasterio (Pisa, Italy). Plasma samples were separated on a native 4–20% Tris-Gly polyacrylamide gel. Western blot analysis was performed with anti-TTR (DAKO) or anti-RBP (Siemens Healthineer) antibodies. Proteins were detected by Clarity ECL substrate (BioRad). Results: Circulating forms of TTR were qualitatively similar between ATTRwt patients at T0 and controls. In both groups, the most represented forms were: TTR dimers or trimers (∼37-50 kDa), TTR tetramers complexed with RBP protein in 1:1 ratio (∼80 kDa, ) or 1:2 ratio (∼100 kDa), and high molecular weight (MW) aggregates (>150 kDa). Neither TTR monomers nor the tetramers were visible. RBP protein was detectable in association with TTR tetramers and some of the higher MW fractions (∼150 kDa, >250 kDa). Following tafamidis treatment, all ATTRwt patients displayed a progressive increase of the intensity of the band corresponding to TTR-RBP complexes, in agreement with the drug stabilizing action on TTR tetramers. Interestingly dimers and trimers, detectable at T0, were progressively lost during tafamidis treatment. Conclusions: The native electrophoretic allowed us to detect several circulating TTR fractions. Data suggest a similar pattern of circulating TTR both in patients and healthy control: TTR tetramer exists only complexed with RBP and in equilibrium with low and high MW forms. Furthermore, the method allowed to appreciate the stabilizing effect of tafamidis on circulating TTR tetramers complexed with RBP. The study of circulating TTR fractions can expand our knowledge on mechanisms triggering its destabilization even when not mutated.